Machine learning‐assisted point‐of‐care diagnostics for cardiovascular healthcare - Kaidong Wang; Bing Tan; Xinfei Wang; Shicheng Qiu; Qiuping Zhang; Shaolei Wang; Ying‐Tzu Yen; Nan Jing; Changming Liu; Xuxu Chen; Shichang Liu; Yan Yu (Bioengineering & Translational Medicine)
Abstract Cardiovascular diseases (CVDs) continue to drive global mortality rates, underscoring an urgent need for advancements in healthcare solutions. The development of point‐of‐care (POC) devices that provide rapid diagnostic services near patients has garnered substantial attention, especially as traditional healthcare systems face challenges such as delayed diagnoses, inadequate care, and rising medical costs. The advancement of machine learning techniques has sparked considerable interest in medical research and engineering, offering ways to enhance diagnostic accuracy and relevance. Improved data interoperability and seamless connectivity could enable real‐time, continuous monitoring of cardiovascular health. Recent breakthroughs in computing power and algorithmic design, particularly deep learning frameworks that emulate neural processes, have revolutionized POC devices for CVDs, enabling more frequent detection of abnormalities and automated, expert‐level diagnosis. However, challenges such as data privacy concerns and biases in dataset representation continue to hinder clinical integration. Despite these barriers, the translational potential of machine learning‐assisted POC devices presents significant opportunities for advancement in CVDs healthcare.